2002
DOI: 10.1016/s0006-3495(02)75339-3
|View full text |Cite
|
Sign up to set email alerts
|

Membrane Protein Crystallization In Meso: Lipid Type-Tailoring of the Cubic Phase

Abstract: Hydrated monoolein forms the cubic-Pn3m mesophase that has been used for in meso crystallization of membrane proteins. The crystals have subsequently provided high-resolution structures by crystallographic means. It is possible that the hosting cubic phase created by monoolein alone, which itself is not a common membrane component, will limit the range of membrane proteins crystallizable by the in meso method. With a view to expanding the range of applicability of the method, we investigated by x-ray diffracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
226
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 160 publications
(246 citation statements)
references
References 51 publications
20
226
0
Order By: Relevance
“…The effect of 10% cholesterol on the lattice parameter of the fully hydrated monoolein cubic Pn3m phase is negligible. 40 Nevertheless, cholesterol may modulate the response of the cubic phase lattice to addition of different ingredients from the crystallization cocktails. Diffusion of β 2 AR(E122W)-T4L in cholesterol-doped LCP at crystallization conditions was on average ~2 times slower in agreement with the rigidifying effect of cholesterol.…”
Section: 44mentioning
confidence: 99%
“…The effect of 10% cholesterol on the lattice parameter of the fully hydrated monoolein cubic Pn3m phase is negligible. 40 Nevertheless, cholesterol may modulate the response of the cubic phase lattice to addition of different ingredients from the crystallization cocktails. Diffusion of β 2 AR(E122W)-T4L in cholesterol-doped LCP at crystallization conditions was on average ~2 times slower in agreement with the rigidifying effect of cholesterol.…”
Section: 44mentioning
confidence: 99%
“…Our findings indicate that the default cubic mesophase is remarkably resilient and retains its phase identity in the presence of a vast array of different additives. These include glycerolipids, cholesterol, free fatty acids, detergents, denaturants, glycerol and thiol-group-specific reagents [22][23][24][25][26][27][28][29][30]. Of course, for each there is a concentration beyond which the cubic phase is no longer stable nor, indeed, useful for crystallogenesis.…”
Section: Mesophase Compatibility With Protein Solution Componentsmentioning
confidence: 99%
“…An alternative was to use monoolein as the hosting lipid and to augment it with typical membrane lipids, thereby creating a more native-like environment. Accordingly, the carrying capacity of the monoolein cubic phase for a number of different lipids was established using SAXS [23]. This amounted to approximately 20 mol% in the case of phosphatidylcholine, phosphadidylethanolamine and cholesterol, with lesser amounts of phosphatidylserine and cardiolipin being accommodated.…”
Section: Additive Lipid Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…In more recent investigations of the aqueous 1-monooleoylglycerol/DOPC mixture [12,13] it has been demonstrated that the fully hydrated (≥ 60 wt.% of water) Pn3m phase of 1-monooleoylglycerol can accommodate up to 25 mol% of DOPC. However, the spectroscopic investigation of these MO/DOPC samples is complicated since two separate phases, aqueous and lipidic, coexist at the excess water condition.…”
Section: Introductionmentioning
confidence: 99%